Psychological Entitlement and Spiritual Entitlement as Correlates of Covid-19 Vaccine Hesitancy Among Students Christian Religious Studies - Uzoigwe, Tobechi; Uzoigwe Chinonso Elvis (MultiTech Publisher, 2024)
This research explored the correlates of psychological entitlement and spiritual entitlement on COVID-19 vaccine hesitancy among students. A cross-sectional research design was adopted to purposely recruit a total population of 97 students studying Christian religious studies from Nasarawa State University The students were administered the Psychological Entitlement Scale, the Spiritual Entitlement Scale, and the Oxford COVID-19 Vaccine Hesitancy Scale. The result showed no significant relationship between psychological entitlement and COVID-19 vaccination hesitancy (r = -.154, p >0.05) and spiritual entitlement and COVID-19 vaccine hesitancy’ (r=.117 at p>0.05) However,the maladaptive subscale showed a significant negative relationship with COVID-19 vaccination hesitancy. The Psychological Entitlement and Spiritual Entitlement Scale jointly predicted COVID-19 vaccine hesitancy (R= .393; F= 8.564, P < .01) It is recommended that future vaccine campaigns engage with religious leaders to appeal to their beliefs and values and encourage them to accept the vaccine. This is the first study to link entitlement mentality with vaccination uptake in Nigeria.